THE INFLUENCE OF SHOPEE PAYLATER USAGE ON IMPULSE BUYING BEHAVIOR WITH HEDONIC LIFESTYLE AS AN INTERVENING VARIABLE AMONG GENERATION Z IN SERDANG BEDAGAI - Padila Putri; Maidalena; Muhammad Lathief Ilhamy Nasution (International Journal of Cultural and Social Science, 2025)
The SPayLater service is a method of paying for purchases on credit that is increasingly popular with the public, especially among Generation Z who are known to have high consumption patterns and tend to be impulsive. This research aims to analyze the effect of using SPayLater on Impulse Buying behavior with Hedonic Lifestyle as an Intervening Variable in Generation Z Serdang Bedagai City. This research uses quantitative methods with an associative approach. Data was collected by distributing questionnaires to 90 respondents who were SPayLater users in Serdang Bedagai City. The data analysis technique used SPSS 30 with a series of statistical tests including path analysis regression tests and hypothesis tests. The results of this research show that (1) SPayLater has a positive and significant influence on Impulse Buying behavior (2) SPaylater has no significant influence on Hedonic Lifestyle (3) Hedonic Lifestyle has a positive and significant influence on Impulse Buying behavior (4) Hedonic Lifestyle was unable to mediate the relationship between SPayLater use and Impulse Buying behavior.